2010
DOI: 10.1002/ardp.201000182
|View full text |Cite
|
Sign up to set email alerts
|

Platinum Complexes with 5‐Methyl‐5(4‐pyridyl)hydantoin and Its 3‐Methyl Derivatives: Synthesis and Cytotoxic Activity – Quantitative Structure‐Activity Relationships

Abstract: 3,5-Dimethyl-5-(4-pyridyl)hydantoin (L) and its platinum(II) and platinum(IV) complexes with the general formula cis-[PtL(2) X(2) ] · n H(2) O and [PtL(2) Cl(4) ], where XCl, I and n = 2-4 were synthesized. A new Pt(IV) complex with 5-methyl-5-(4-pyridyl)hydantoin (L') with the formula cis-[Pt(L')(2) Cl(2) (OH)(2) ] · 5 H(2) O was also synthesized. The novel compounds were characterized by elemental analysis, IR, (1) H-, (13) C-, (195) Pt-NMR spectra and molar conductivity. The cytotoxic effects of these comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…This indicates that the pyridine nitrogen atom participates in the coordination with platinum in all new platinum(II) complexes. These observations are in accordance with previously studied and published Pt(II) complexes with 3-amino-5-methyl-5-(4-pyridyl)hydantoin (1), 5-methyl-5-(4-pyridyl)hydantoin (2), 3,5-dimethyl-5-(4-pyridyl)hydantoin (3) [20,26,27].…”
Section: Ir Spectrasupporting
confidence: 94%
See 2 more Smart Citations
“…This indicates that the pyridine nitrogen atom participates in the coordination with platinum in all new platinum(II) complexes. These observations are in accordance with previously studied and published Pt(II) complexes with 3-amino-5-methyl-5-(4-pyridyl)hydantoin (1), 5-methyl-5-(4-pyridyl)hydantoin (2), 3,5-dimethyl-5-(4-pyridyl)hydantoin (3) [20,26,27].…”
Section: Ir Spectrasupporting
confidence: 94%
“…Structure-cytotoxicity relationship studies revealed that for many compounds increased lipophilicity is often accompanied by increased cytotoxicity [25]. Taking into account our previous experience with cytotoxic platinum(II) complexes, carrying hydantoin ligands [26,27] and the approach for increasing lipophilicity via alkylation, herein we have prepared more lipophilic 3-subsituted-5-methyl-5-(4-pyridyl) hydrations and their Pt(II) complexes. The present study represents the synthesis, physicochemical evaluation and pharmacological investigation of three new Pt(II) complexes with 3-ethyl-5-methyl-5-(4-pyridyl)hydantoin (4), 3-propyl-5-methyl-5-(4-pyridyl)hydantoin (5) and 3-benzyl-5-methyl-5-(4-pyridyl)hydantoin (6) with general formula cis-[Pt(L) 2 Cl 2 ].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Many Pt(II) and Pt(IV) compounds are investigated in vitro for antitumor effects. [93][94][95][96] At present, it is a rule to consider that the antitumor activity of the platinum-containing anticancer preparations is associated with DNA platination. [97] The antitumor properties of Pt(II) complexes are supposed to be strongly dependent on the character of bond between different ligands and the metal.…”
Section: Metal Complexesmentioning
confidence: 99%
“…Over the last few years we have been synthesized and studied for cytotoxicity in vitro some Pt(II) and Pt(IV) complexes with different hydantoin and spirohydantoin derivatives [16][17][18]. Some of them have similar cytotoxic activity to referent antitumor agent cisplatin.…”
Section: Introductionmentioning
confidence: 98%